Limited directional change in mountaintop plant communities over 19 years in western North America - Goff, Kaleb A.; Oldfather, Meagan F.; Nachlinger, Jan; Smithers, Brian V.; Koontz, Michael J.; Bishop, Catie; Bishop, Jim; Burke, Mary T.; Sheth, Seema N. (Ecosphere (Washington, D.C), 2025)
Plant communities on mountain summits are commonly long‐lived, cold‐adapted perennials with low dispersal ability. These characteristics in tandem with limited area to track suitable conditions make these mountain communities potentially highly vulnerable to climate change, and indicators of climate change impacts. We investigated temporal changes in plant communities on 29 arid mountain summits across eight study regions in California and Nevada, USA, over 19 years. We analyzed community dynamics in terms of species richness, turnover, gain and loss of functional groups, and relative abundance of functional groups. First, across all summits and regions, we found no change in species richness over time. Second, there was relatively high species turnover (21.7%) between the five‐year survey intervals, but turnover was not significantly different from random expectation. Within functional groups, forbs had the greatest proportion of gains and cushions had the greatest proportion of losses. Third, qualitative abundance categories presented a small but consistent signal of decrease in the relative abundance of cushions, graminoids, and shrubs/trees over the study period. Across a broad geographic scale and nearly two decades, community patterns were widely similar, suggesting that climate change has not impacted local colonization or extirpation of mountaintop species in this arid region. These findings support observed differences in response to climate change between temperature‐limited and water‐limited regions globally, and highlight the lagged and variable nature of high‐elevation systems. Our findings fill a major data gap on alpine plant community responses to climate change in the western United States and bolster the importance of long‐term ecological monitoring with rapid climate change.